The effect of different treatment to overcome seed dormancy of indica rice / Mohamad Noor Saza Ishak - Ishak, Mohamad Noor Saza (Faculty of Plantation and Agrotechnology, 2019)
The study was conducted to determine the effect of different treatment to overcome seed dormancy of Indica rice. The objectives were to increase the germination rate of the storage seed with different treatment and to determine dormancy of different varieties of Indica rice seed. Three Indica rice was obtained from MARDI (cv. MRIA), cv. MR297 from KADA and cv. MR220 from BERNAS. All the seed have been storage about 5 to 6 weeks after harvest under normal room temperature (20-25oC). Seed have been treated with four treatments which were T1 (control), T2 (2% H2O2), T3 (GA3) and T4 (heat treatment). Result showed that there was interaction between germination percentages of Indica rice under different treatments. T1 (control), was achieved 100% for cv. MR1A, 99% for cv. MR297 and 0% for cv. MR220. T2 (H2O2) was achieved 100% for cv. MR1A, 99% for cv. MR297 and 0% for cv. MR220. T3 (GA3) was achieved 100% for cv. MR1A, 97% for cv. MR297 and 0% for cv. MR220. T4 (heat) was achieved 100% for cv. MR1A, 97% for cv. MR220 and 85% for cv. MR220. The treatment of Indica rice with control, 2% H2O2, GA3 and heat treatment, significantly increase the germination rate of paddy seed. Among the treatment, heat treatment is more effective in increasing seed germination percentage compare to other treatment.